Intraguild interactions between the predatory hoverfly Episyrphus balteatus (Diptera: Syrphidae) and the Asian ladybird, Harmonia axyridis (Coleoptera: Coccinellidae): Effect of larval tracks - Almohamad, R.,Liege Univ., Gembloux (Belgium). Dept. of Functional and Evolutionary Entomology; Verheggen, F.J.,Liege Univ., Gembloux (Belgium). Dept. of Functional and Evolutionary Entomology; Francis, F.,Liege Univ., Gembloux (Belgium). Dept. of Functional and Evolutionary Entomology; Haubruge, E.,Liege Univ., Gembloux (Belgium). Dept. of Functional and Evolutionary Entomology (European journal of entomology, 2010)
The effects of the larval tracks of Episyrphus balteatus and Harmonia axyridis on the egg laying behavior of females of the predatory hoverfly E. balteatus were investigated in two-choice experiments. The oviposition response of H. axyridis to larval tracks of E. balteatus was also tested in one-choice experiments. Gravid E. balteatus females laid significantly fewer eggs on leaf discs with aphids and contaminated with tracks of conspecific or heterospecific larvae than on control leaf discs. H. axyridis females laid similar numbers of eggs in Petri dishes with aphids and contaminated with the tracks of E. balteatus larvae as in control Petri dishes. This indicates that E. balteatus females lay fewer eggs at sites where there are conspecific and heterospecific larval tracks, whereas the tracks of the syrphid larvae did not deter H. axyridis females from laying eggs.